Tri‐Diketopyrrolopyrrole Molecular Donor Materials for High‐Performance Solution‐Processed Bulk Heterojunction Solar Cells. (15th August 2013) - Liu, Jianhua; Sun, Yanming; Moonsin, Preecha; Kuik, Martijn; Proctor, Christopher M.; Lin, Jason; Hsu, Ben B.; Promarak, Vinich; Heeger, Alan J.; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Two new high‐performance DPP‐containing donor molecules employing a molecular architecture with three DPP chromorphores (tri‐DPP) in conjugated backbones are synthesized and characterized. The two tri‐DPP molecules with only a structural difference on alkyl substitutions, when blended with PC71BM, lead to power conversion efficiencies up to 4.8 and 5.5%, respectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>